Matrix Metalloproteinase 9 Secreted by Hypoxia Cardiac Fibroblasts Triggers Cardiac Stem Cell Migration In Vitro - Qing Gao; Maojuan Guo; Wenyun Zeng; Yijing Wang; Lin Yang; Xiaoli Pang; Huhu Li; Yanrong Suo; Xijuan Jiang; Chunquan Yu (Hindawi Limited, 2015)
Cessation of blood supply due to myocardial infarction (MI) leads to complicated pathological alteration in the affected regions. Cardiac stem cells (CSCs) migration plays a major role in promoting recovery of cardiac function and protecting cardiomyocytes in post-MI remodeling. Despite being the most abundant cell type in the mammalian heart, cardiac fibroblasts (CFs) were underestimated in the mechanism of CSCs migration. Our objective in this study is therefore to investigate the migration related factors secreted by hypoxia CFs in vitro and the degree that they contribute to CSCs migration. We found that supernatant from hypoxia induced CFs could accelerate CSCs migration. Four migration-related cytokines were reported upregulated both in mRNA and protein levels. Upon adding antagonists of these cytokines, the number of migration cells significantly declined. When the cocktail antagonists of all above four cytokines were added, the migration cells number reduced to the minimum level. Besides, MMP-9 had an important effect on triggering CSCs migration. As shown in our results, MMP-9 induced CSCs migration and the underlying mechanism might involve TNF-α signaling which induced VEGF and MMP-9 expression.